ANALISA LATAR BELAKANG PENDIDIKAN GURU TERHADAP METODE MENGAJAR DI KELAS - Puteri, Ika Apriati Widya; Puteri , Ika Apriati Widya (incrementapedia, 2021)
Nowadays, there are still many kindergarten teachers who do not have an early childhood education background. Whereas the appropriate educational background can be related to the level of achievement of children's development and related to the achievement of learning in early childhood.The purpose of this study was to determine whether educational background affects teaching methods in the KB & TK Islam Silmi Samarinda. The research use qualitative research approach such as interview, observation, and documentation. The technique used in this triangulation is triangulation of data sources which checks the validity of the data by checking or as a comparison against 3 sources. The results of research conducted by researchers at KB & TK Islam Silmi Samarindashow that teachers with early childhood education background look more optimal by using varied teaching methods than those without this background. The teacher also have more knowledge about teacher’s professional competence compare to teacher who don’t have the early childhoode education background.